Phytochemical Screening by HPLC and FTIR Spectroscopy of Glucokinin Isolated from Methanol Extract of Bauhinia Variegata (Medico Legal Update, 2020)
The isolation of active plants compounds lead to discover a several drugs derived directly from plants. In thecurrent study, the Glucokinin was isolated and purified from the methanol leave extract of medicinal plantBauhinia variegate, the attempts to identified and characterized it’s functional groups by the HPLC and FTIRspectroscopy was worked in this study. By using FT-IR spectroscopic the Glucokinin shown differentfunctional groups. The FTIR spectrum of the purified material, Glucokinin from the methanol leaf extractof B. variegata indicate the presence of different functional groups. The peak near 1650 cm-1 is the amideI band.